عقوبة النفي السياسي وأسبابه في العهد البويهي "334-447 هـ. / 945-1055 م." - عبدالجبورى، على حميد (جامعة تكريت - كلية التربية للعلوم الإنسانية, 2023)
اتخذ البويهيون عقوبة النفي لعقاب وتأديب وإبعاد الخارجين عليهم، وطالت هذه العقوبة الكثير من الأمراء البويهيين وقادة الجيش وغيرهم من رجال الدين، وجاء إعلان هؤلاء القادة تمردهم وعصيانهم على سلطة الأمير البويهي، بسبب اتباعه سياسة التمييز والانحياز إلى صف الأتراك، محاولين إقصاء الجند الديلمي وأمرائهم من جهة ومن جهة أخرة كان لطمع بعض القادة في انتزاع الإمارة منه لصالحهم، مستغلين مراكزهم العسكرية، لان جميع الجند كانوا تحت إمرتهم، أما سبب اتخاذ هذه العقوبة لما لها الأثر في النفس بإبعاد المنفي عن أهله وبلده وعزله عن مؤيديه وأنصاره وإذلاله، وتأمين جانبهم من العودة إلى العصيان مرة ثانية. The Buyids punished, controlled, and banished those who disobeyed them by sending them into exile. This punishment affected a large number of Buyid princes, military commanders, and clerics. On the one hand, the announcement of these leaders' rebellion and disobedience against the authority of the Buyid prince was due to the prince's ensuing policy of discrimination and siding with the Turks, attempting to exclude the Daylamite soldiers and their princes. On the other hand, it was the greed of certain leaders to seize the emirate from him for their own benefit, taking advantage of their military positions, since all the soldiers were under their command. Rebellion again.
Keywords: النفي السياسي -- الدولة البويهية -- التاريخ الإسلامي